2014
DOI: 10.1007/s11999-014-3474-4
|View full text |Cite
|
Sign up to set email alerts
|

Outcome After Reconstruction of the Proximal Humerus for Tumor Resection: A Systematic Review

Abstract: Background Tumors of the appendicular skeleton commonly affect the proximal humerus, but there is no consensus regarding the best reconstructive technique after proximal humerus resection for tumors of the shoulder. Questions/purposes We wished to perform a systematic review to determine which surgical reconstruction offers the (1) best functional outcome as measured by the Musculoskeletal Tumor Society (MSTS) score, (2) longest construct survival, and (3) lowest complication rate after proximal humerus resect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
95
1
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 117 publications
(110 citation statements)
references
References 49 publications
4
95
1
4
Order By: Relevance
“…However, our previous review of the literature and the published experience from our group, report a comparable rate of infection in the proximal humerus between endoprostheses, osteoarticular allografts, and APCs. We found a higher complication rate and need for revision with the use of osteoarticular allografts in the proximal humerus due to a higher rate of fractures of the allograft instead of infection . The vast majority of the literature on massive allograft reconstruction of the humerus focuses on the proximal humerus and is limited by small sample sizes.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…However, our previous review of the literature and the published experience from our group, report a comparable rate of infection in the proximal humerus between endoprostheses, osteoarticular allografts, and APCs. We found a higher complication rate and need for revision with the use of osteoarticular allografts in the proximal humerus due to a higher rate of fractures of the allograft instead of infection . The vast majority of the literature on massive allograft reconstruction of the humerus focuses on the proximal humerus and is limited by small sample sizes.…”
Section: Introductionmentioning
confidence: 88%
“…The humerus is a relatively common location for tumors of the bone . Several options for reconstruction after resection are available depending on the location of the tumor . Alternatives for mobile reconstruction include endoprostheses (EP), allograft‐prosthesis composites (APCs), and osteoarticular/intercalary allograft reconstruction; each of these techniques having its advantages and disadvantages.…”
Section: Introductionmentioning
confidence: 99%
“…Extirpation of tumor tissue is expected to cause some degree of functional impairment; therefore, efforts should be made to decrease such impairment. Studies have reported on the functional outcomes of impairments on musculoskeletal tumor treatment [9,10,14,16,17,19,21].…”
Section: Introductionmentioning
confidence: 99%
“…Since then, this system has been used in numerous studies to evaluate functional outcomes [9,10,14,16,17,19,22], making it one of the most widely used functional evaluation tools. The original scoring system was written in English and subsequently has been translated into Brazilian Portuguese and Japanese.…”
Section: Introductionmentioning
confidence: 99%
“…Options following resection include allograft reconstruction, arthroplasty, and definitive resection with flail shoulder/resection arthroplasty . Hemiarthroplasty and allograft prosthetic composite with hemiarthroplasty have been the workhorse reconstruction with low complication rates and below shoulder level function . However, there are typically substantial functional deficits associated with this reconstruction .…”
Section: Introductionmentioning
confidence: 99%